Distribution and concentration of cyclosporin in human blood. Issue 10 (October 1984) - Atkinson, K; Britton, K; Biggs, J
Abstract : In patients receiving cyclosporin to minimise graft versus host disease after allogeneic bone marrow transplantation, whole blood cyclosporin concentration was roughly twice the serum concentration when blood was separated at 37 degrees C. In turn, blood separation at 37 degrees C resulted in a doubling of serum cyclosporin concentration compared with separation at room temperature. In vitro studies showed that the latter phenomenon was due to a temperature dependent partitioning of cyclosporin between plasma and red cells, such that increased cyclosporin was taken up from the serum into red cells at room temperature. Increasing delay in separation of patient blood (at either temperature) resulted in a gradually increasing cyclosporin serum concentration. Further in vitro studies showed that a distribution equilibrium between blood components was reached within 30 min incubation. Red cell uptake of cyclosporin was saturable at an incubation concentration of greater than 4 microgram/ml, while plasma and mononuclear cells showed a linear uptake to 7 micrograms/ml. The cellular cyclosporin content of a mononuclear cell was roughly 1000 times greater than that of an erythrocyte. For clinical monitoring we recommend the measurement of cyclosporin concentration either in whole blood or in serum separated at 37 degrees C without delay after venepuncture.